Budget Deficit Sustainability of Bangladesh - Rahman, Mohammad Mahbubur (Asian Development Policy Review, 2017)
Budget deficiency has become a regular phenomenon in the fiscal policy of Bangladesh since its inception. In recent times the amount of deficiency has been accounted to a considerable amount and showing an upward trend which has drawn attention of various sector intelligence including media. Hence, we became interested to analyze the sustainability of the budget deficit of the central government of Bangladesh. We have applied various methods to check both the strong form of sustainability and long run sustainability. To check the strong form of sustainability, we have used government budget deficit to GDP ratio as our concern variable and we have applied standard unit root tests. Subsequently we have checked the long run sustainability by applying Johansen co-integration test and Quintos (1995) approach based on governmental IBC (Inter-temporal Budget Constraint). In co-integration test and Quintos (1995) approach we have used Government revenue to GDP ratio and Government expenditure to GDP ratio as our concern variable. We have covered a sample period from 1972 to 2012. Both types of test tell us that the government budget deficit in Bangladesh is sustainable.